Green Tea Extract Induces the Resistance of Caenorhabditis elegans against Oxidative Stress - Sami Abbas; Michael Wink (MDPI AG, 2014)
Epidemiological studies on the effects of green tea consumption (Camellia sinensis) have demonstrated a reduction for the risk of age-related diseases. The investigation of the in vivo and in vitro antioxidant properties of an aqueous extract of green tea (GTE) was the aim of the current study. 2,2-Diphenyl-1-picrylhydrazyl (DPPH•) and superoxide anion radical (O2•−) assays were used to estimate the GTE antioxidant activity. To investigate the protective effects of GTE against oxidative stress, wild-type N2 and transgenic strains (TJ374, hsp-16.2/GFP) of the model organism, Caenorhabditis elegans (C. elegans), were chosen. In the current study, the following catechins were identified by LC/ESI-MS: catechin, epicatechin, epicatechin gallate, gallocatechin, epigallocatechin and epigallocatechin gallate. GTE exhibited a free radical scavenging activity of DPPH• and O2•− with IC50 8.37 and 91.34 µg/mL, respectively. In the C. elegans strain (TJ374, hsp-16.2/GFP), the expression of hsp-16.2/GFP was induced by a nonlethal dose of juglone, and the fluorescence density of hsp-16.2/GFP was measured. The hsp-16.2/GFP was reduced by 68.43% in the worms pretreated with 100 µg/mL GTE. N2 worms pretreated with 100 µg/mL GTE exhibited an increased survival rate of 48.31% after a lethal dose application of juglone. The results suggest that some green tea constituents are absorbed by the worms and play a substantial role to enhance oxidative stress resistance in C. elegans.